A 5-fluorouracil–kaempferol drug–drug cocrystal: a ternary phase diagram, characterization and property evaluation. Issue 46 (12th November 2020) - Lv, Wen-Ting; Liu, Xiao-Xu; Dai, Xia-Lin; Long, Xiang-Tian; Chen, Jia-Mei
Abstract : A drug–drug cocrystal of 5-fluorouracil and kaempferol was comprehensively investigated and exhibits optimized solubility behavior in comparison with individual APIs. Abstract : The synergistic anti-tumor effect of a typical chemotherapy drug, 5-fluorouracil, and a natural flavonoid compound, kaempferol, has been reported recently. However, the oral absorption of 5-fluorouracil is incomplete and nonuniform for different individuals due to fast metabolism and an obvious peak-valley phenomenon, while kaempferol has very poor solubility and this consequently leads to low oral bioavailability. The weakness of each drug greatly restricts the potential of anti-tumor drug combination in the clinical application. In this work, a new 1 : 1 drug–drug cocrystal of 5-fluorouracil and kaempferol was successfully prepared by liquid assisted grinding, slurry conversion crystallization and evaporation crystallization. A ternary phase diagram was constructed to gain some insights into the thermodynamics of the cocrystal system. The obtained cocrystal was comprehensively characterized by single crystal and powder X-ray diffraction, differential scanning calorimetry and thermogravimetric analysis, as well as Fourier transform infrared and nuclear magnetic resonance spectroscopy. The drug–drug cocrystal enhances the stability of kaempferol and optimizes the dissolution behavior of each single component as compared to pristine drugs. Therefore, the 5-fluorouracil–kaempferol cocrystal has the potential to be developed as efficient oral formulations for drug combination which will overcome the weaknesses of each parent drug.